An interval multiobjective approach considering irrigation canal system conditions for managing irrigation water - Zhang, Fan; Guo, Shanshan; Zhang, Chenglong; Guo, Ping (Journal of cleaner production, 2019)
In order to consider irrigation canal system conditions in irrigation-water management, this study developed an interval multiobjective approach for helping irrigation-water managers solve the multiobjective problem under interval uncertainty in the process of allocating limited irrigation water. Irrigation canal system conditions in this study mainly refer to canals distribution reflected by topological relations between canals and irrigation districts, and canals seepage estimated by multiple linear regression model. The proposed approach could address the conflicting objectives under interval uncertainty and help irrigation-water managers obtain more practical allocation schemes. This approach was applied to the middle reaches of Heihe River basin for allocating limited irrigation water among multiple irrigation districts (IDs) to demonstrate its applicability and practicality. Through the proposed approach, three different objectives were coordinated. These obtained results can not only display the amount of water allocated to each ID and canal but also show the amount of seepage from canals and field. From the optimized results, local water managers could obtain both better irrigation-water allocation scheme and find out the limited points of canals for IDs’ future development. Additionally, two comparisons illustrated that the results obtained by proposed approach are more practical than single objective with the same constraints and the interval multiobjective programming (IMP) model without considering canal system conditions in allocating irrigation water among IDs. This approach is valuable for improving the feasibility of optimal results in irrigation-water management, and it provides a possible way to take these important factors into account for related researches. •An interval multiobjective approach is developed considering irrigation canal system conditions.•The proposed approach can improve the practicality of the optimized schemes in practice.•This approach is applied to a case study for planning limited irrigation water.•The results offer operable allocation schemes for local irrigation-water managers to improve agricultural production ability.